2021
DOI: 10.3389/fsurg.2021.621525
|View full text |Cite
|
Sign up to set email alerts
|

Bile Microbiota in Liver Transplantation: Proof of Concept Using Gene Amplification in a Heterogeneous Clinical Scenario

Abstract: Objective: Historically, bile in the biliary tract has been considered sterile. Most of the series are based on patients with biliary tract diseases or the bile has been obtained with procedures susceptible to contamination.Methods: We evaluated the bile in a heterogeneous cohort of liver donors and recipient patients, with samples obtained in a sterile way, directly from the gallbladder and the common bile duct.Results: We assessed the bile microbiota in six liver donors and in six liver recipients after whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…However, due to the fact of ethical issues, there are currently a small number of studies on biliary microbiota in healthy people. This aspect of research is mainly conducted by replacing the biliary tract of healthy people with the biliary tract of LT donors and patients with pancreatic disease without hepatobiliary disease [36][37][38][39]. Therefore, it is difficult to compare biliary microbiota after transplantation with those in healthy people.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the fact of ethical issues, there are currently a small number of studies on biliary microbiota in healthy people. This aspect of research is mainly conducted by replacing the biliary tract of healthy people with the biliary tract of LT donors and patients with pancreatic disease without hepatobiliary disease [36][37][38][39]. Therefore, it is difficult to compare biliary microbiota after transplantation with those in healthy people.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with a previous study demonstrating that bile of the liver graft from deceased donor was negative for bacteria by using 16S ribosomal RNA sequencing. [22] In addition, the bacteria most frequently detected in bile produced from the diseased liver are Gram negative such as Escherichia coli and Klebsiella. [23] These bacteria were not detected after BDA in the current study and further supported that bacterial contamination of bile in the diseased liver is not a significant risk after the complete extraction of the whole diseased liver.…”
Section: Discussionmentioning
confidence: 99%
“…In this research study, there was no control group of healthy subjects because there are ethical concerns [ 68 , 69 ] related to the risks associated with the ERCP procedure [ 70 ]. In addition, a recent study by D’Amico at al., showed that the bile samples studied by rDNA sequence analysis of multiorgan donors who have not undergone any previous biliary procedures and have no biliary abnormalities is sterile [ 71 ].…”
Section: Limits Of the Studymentioning
confidence: 99%